2016
DOI: 10.1177/1535370216641786
|View full text |Cite
|
Sign up to set email alerts
|

The common variant Q192R at the paraoxonase 1 (PON1) gene and its activity are responsible for a portion of the altered antioxidant status in type 2 diabetes

Abstract: In this study, we investigated the effects of paraoxonase 1 (PON1) activities and the variant PON1-Q192R on the ferric reducing ability of plasma (FRAP) and total thiol. In addition, we examined the distribution of genotypes of this variant and the relationship of the genotypes with age in patients with type 2 diabetes (T2D). A total of 115 patients with T2D were enrolled in this study. Paraoxonase activity (PON-para) and arylesterase activity (PON-aryl) were determined using spectrophotometric assays. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In a study conducted on a group of individuals with cardiovascular disease, the G allele frequency of PON1 rs662 was higher in the patient group, but no statistically significant difference was found than the healthy individuals. 35 In another study, the relation between cardiovascular diseases and PON1 rs662 and rs854560 polymorphisms was investigated. The T allele frequency of PON1 rs854560 was higher in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on a group of individuals with cardiovascular disease, the G allele frequency of PON1 rs662 was higher in the patient group, but no statistically significant difference was found than the healthy individuals. 35 In another study, the relation between cardiovascular diseases and PON1 rs662 and rs854560 polymorphisms was investigated. The T allele frequency of PON1 rs854560 was higher in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…High HTLase activity has been reported to provide better protection against protein homocysteinylation compared to low HTLase activity (7). Recent studies have demonstrated that PON-1 and ARE are enzymes in the esterase group that are encoded by the same gene and whose active centres are similar (14, 15). Although PON-1 is known to present polymorphic changes, ARE enzyme does not show any genetic polymorphism (16).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, higher frequencies of Q allozymes (0.78) was previously reported by Zargari et al (2016) Hernández-Díaz et al (2016) who revealed that the 192Q allele carriers are at high risk to develop CAD. On the other hand, in another study , Bounafaa et al (2015) reported that the PON1 R allele is abundant in CHD patients, indicating that the PON1192 polymorphism may be a risk factor for atherosclerosis.…”
Section: Discussion:-mentioning
confidence: 66%